1977
DOI: 10.1159/000198043
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Gastric Electrical and Mechanical Activity by Intraduodenal Agents in Pigs and the Effects of Vagotomy

Abstract: Miniature pigs were chronically implanted with gastric electrodes, strain gauge devices allowing the measurement of circular contractions in the antrum and body of the stomach, and with a duodenal catheter through which duodenal infusions were administered. Inhibition of gastric motility by intraduodenal agents was measured before and after truncal vagotomy in conscious animals 20 min after feeding of a normal meal. The agents infused in the duodenum (10 ml/min, 4 min), were: HC1 75 mEq/l (A), glucose 100 g/l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Disruption of cyclical MMCs in the small intestine following intraduodenal cholera toxin or mannitol was correlated with an inhibition of gastric motility, possibly due to the vagally mediated inhibition of gastric motility seen after introduction of various chemical agents into the duodenum [17] or more simply to duodenogastric reflux. Stim ulation of colonic motility following intraduodcnal infusion of hypertonic solutions is probably attributable to arrival of large quantities of fluids in the colon since the vol ume of the colonic contents constitutes one of the most efficacious stimulants of colonic motility [7], No colonic stimulation was seen following administration of cholera toxin, probably because an insufficient volume of secreted fluids reached the colon; this is in agreement with the absence of diarrhoea fol lowing administration of cholera toxin at this dose.…”
Section: Discussionmentioning
confidence: 98%
“…Disruption of cyclical MMCs in the small intestine following intraduodenal cholera toxin or mannitol was correlated with an inhibition of gastric motility, possibly due to the vagally mediated inhibition of gastric motility seen after introduction of various chemical agents into the duodenum [17] or more simply to duodenogastric reflux. Stim ulation of colonic motility following intraduodcnal infusion of hypertonic solutions is probably attributable to arrival of large quantities of fluids in the colon since the vol ume of the colonic contents constitutes one of the most efficacious stimulants of colonic motility [7], No colonic stimulation was seen following administration of cholera toxin, probably because an insufficient volume of secreted fluids reached the colon; this is in agreement with the absence of diarrhoea fol lowing administration of cholera toxin at this dose.…”
Section: Discussionmentioning
confidence: 98%
“…There are several reports which either directly (Mei, 1978;Hardcastle, Hardcastle & Stanford, 1978;Sharma & Nasset, 1962) or indirectly (Leek, 1972;Bell & Watson, 1976;Roze, Couturier, Chariot & Debray, 1977;Henderson, Jefferys, Jones & Stanley, 1976;Cabanac, 1971;Cabanac & Duclaux, 1973) suggested the existence of glucoreceptors in the digestive tract. However, the main difference between 'glucose sensors' in the liver and glucoreceptors in the digestive tract is that the latter increase their rate of discharge in response to glucose, in contrast to the former which decrease their rate of firing.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong functional evidence for vagus nerve pathways mediating chemosensory responses from the intestine. Early studies revealed that disruption of vagal pathways via subdiaphragmatic vagotomy or afferent denervation largely or completely blocked inhibition of gastric emptying, gastric acid secretion, and food intake in response to intestinal nutrient exposure in animals and humans (Wilkinson and Johnston, 1973; Roze et al, 1977; Raybould and Holzer, 1992; Schwartz et al, 1993). Over subsequent years, considerable progress has been made in understanding the activation and connectivity of vagus nerve pathways involved in nutrient reflexes, and their subsequent control of glycemia, food intake, and satiety (Raybould, 1991, 2010; Zittel et al, 1994; Lavin et al, 1996; Imeryuz et al, 1997; Broberger and Hokfelt, 2001; Blackshaw et al, 2007).…”
Section: Introductionmentioning
confidence: 99%